Lipocortin 1 (annexin 1): a candidate paracrine agent localized in pituitary folliculo-stellate cells. - Traverso, V; Christian, H; Morris, J; Buckingham, J (1999)
It is now well established that lipocortin 1 (LC1) plays an important role as a mediator of early delayed glucocorticoid feedback action in the hypothalamo-hypophysial system. In both the hypothalamus and anterior pituitary gland, LC1 mimics some of the actions of glucocorticoids; moreover, glucocorticoids stimulate the synthesis of LC1 and cause the translocation of intracellular LC1 to the outer cell surface. The mechanism by which LC1 acts in these tissues is only partially understood, but may involve paracrine and/or autocrine actions. To address these possibilities we have investigated the localization of LC1 in the rat pituitary gland, using double labeling immunohistochemistry to identify the pituitary cell types that express LC1. At the light microscopic level LC1 was not detected in the endocrine cells in cryosections of the pituitary, but it was found in abundance in the surrounding folliculo-stellate (FS) cells. In the anterior and interme diate pituitary lobes, there was a near total colocalization of LC1 and S100, a specific marker of FS cells. By contrast, in the posterior pituitary gland, LC1 immunoreactivity was not colocalized with S100 which labeled most pituicytes, or with OX-42 monoclonal antibody, a marker of the microglial cells. Immunogold electron microscopy confirmed that LC1 is present in the nongranulated FS cells. LC1 im munoreactivity was also present in a mouse pituitary FS-like cell line (TtT/GF), particularly in the periphery of the cytoplasm. The localization of LC1 in the FS cells of the anterior pituitary gland defines LC1 as a new marker of the FS cell population. These results support our hypothesis that LC1 acts as one of the paracrine agents liberated by FS cells that modulate the release of pituitary hormones.